Descriptions of unknown sexes of Theraphosidae spiders (Mygalomorphae: Plesiopelma, Tmesiphantes) from northern Argentina - Beratz, Matías Joel (2025)
Females previously unknown from two Argentinean tarantula (Theraphosidae), Plesiopelma paganoi Ferretti & Barneche, 2014 and Tmesiphantes crassifemur (Gerschman & Schiapelli, 1960) are here described. Both specimens were collected at the type locality or very close to it to assure to be conspecific. The female of P. paganoi can be distinguished from congeners by the high number of labial and maxillary cuspules and the shape of the spermathecae with very short and non-spiraled ducts. The female of T. crassifemur is characterized by the shape of the spermathecae and the absence of spiniform setae on coxa III and IV. New diagnoses and a distribution map for both species are presented.